Empowering the data science scientist - Moore, Jason H. (BioData mining, 2021)
[...]data scientists are experts at data and knowledge integration and analysis. [...]being able to see and understand the downstream analytics pipeline could help the data scientist articulate questions which can be answered thus improving the likelihood of success. [...]we must provide federal and private funding opportunities for data scientists to be able to collect, integrate, and synthesize the data and knowledge sources from across domains. [...]we need to provide the recognition and rewards to encourage data scientists to take on data science scientist roles.